Role of the Lateral Habenula in Pain-Associated Depression - Li, Yanhui; Wang, Yumeng; Xuan, Chengluan; Li, Yang; Piao, Lianhua; Li, Jicheng; Zhao, Hua (Frontiers in Behavioral Neuroscience, 2017)
Patients with chronic pain have significantly higher incidences of depression and anxiety than the average person. However, the mechanism underlying this link has not been elucidated in terms of how chronic pain causes significant mood changes and further develops into severe anxiety or depression. The serotonergic system in the raphe nuclei is an important component in both pain processing and the pathogenesis of depression. Since the lateral habenular nucleus (LHb) controls the raphe nuclei, it may participate in the regulation of pain-associated depression. Thus, the aim of the current study was to investigate the role of the LHb in this pathophysiological process. We used chronic constriction injury (CCI) of the sciatic nerve in rats as a model for neuropathic pain and assessed the changes potentially related to the mood disorders. The forced swim test and sucrose preference test were performed to determine the behavioral changes 28 days after pain surgery. Expression of β calmodulin-dependent protein kinase type II (βCaMKII) in the LHb, cytochrome-c oxidase activity in the LHb and dorsal raphe nucleus (DRN), and serotonin (5-HT) levels in the DRN were measured. We found an increasing in LHb activity and βCaMKII expression, and a decrease in neuronal activity in the DRN and 5-HIAA/5-HT ratios in the CCI rats. These effects were accompanied by the depression-like behaviors. Lesions in the LHb improved the pain threshold and depression-like behavior in the rats. These results suggest that the LHb may play a role in pain-associated depression by affecting the activity of 5-HT neurons in the DRN. Furthermore, we showed that increases in the LHb-DRN pathway activity were a common neurobiological mechanisms for pain and depression, which may explain the coexistence of pain and depression.